2000
DOI: 10.1016/s0092-8674(00)00196-3
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Functional Analysis of Ras Binding to Its Effector Phosphoinositide 3-Kinase γ

Abstract: Ras activation of phosphoinositide 3-kinase (PI3K) is important for survival of transformed cells. We find that PI3Kgamma is strongly and directly activated by H-Ras G12V in vivo or by GTPgammaS-loaded H-Ras in vitro. We have determined a crystal structure of a PI3Kgamma/Ras.GMPPNP complex. A critical loop in the Ras binding domain positions Ras so that it uses its switch I and switch II regions to bind PI3Kgamma. Mutagenesis shows that interactions with both regions are essential for binding PI3Kgamma. Ras al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
502
5
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(538 citation statements)
references
References 60 publications
(1 reference statement)
24
502
5
2
Order By: Relevance
“…The fraction of this region provided by ␤-strand 2 as well as part of ␤-strand 1 and potentially the C-terminal end of ␣-helix 1 may, as has been observed for the RalGDS (Fig. 3B) and the PI3K Ras-binding domain (31)(32)(33), mediate the interaction with complementary negatively charged patches in the switch I and II regions of a regulatory GTPase. The F0 domain of the protein talin, an actinbinding protein involved in integrin activation, also shows a ubiquitin-like fold, including a similar although smaller positive surface patch.…”
Section: Resultsmentioning
confidence: 70%
“…The fraction of this region provided by ␤-strand 2 as well as part of ␤-strand 1 and potentially the C-terminal end of ␣-helix 1 may, as has been observed for the RalGDS (Fig. 3B) and the PI3K Ras-binding domain (31)(32)(33), mediate the interaction with complementary negatively charged patches in the switch I and II regions of a regulatory GTPase. The F0 domain of the protein talin, an actinbinding protein involved in integrin activation, also shows a ubiquitin-like fold, including a similar although smaller positive surface patch.…”
Section: Resultsmentioning
confidence: 70%
“…[19][20][21][22] Ras can then induce membrane localization and activation of the p110 subunit of PI3K, as determined by crystal structure studies. 23 Specifically, this interaction occurs between regions on Ras, known as switch I (residues 33-41) and switch II (residues 63, 64, and 73), which bind to a sequence on PI3K-g referred to as the Ras-binding domain (RBD). 24 It was recently shown that the PI3K regulatory subunit, p85, contains two additional regulatory domains: a GTPase-responsive domain (GRD) that can mediate PI3K activation through binding small GTPases (Ras, Rac1), and an inhibitory domain that can block these binding events.…”
Section: Cytokine Activation Of Pi3k/akt Pathwaymentioning
confidence: 99%
“…The Class 1 PI3-Ks are responsible for the synthesis of the intracellular PtdIns (3,4)P 2 and Ptdlns (3,4,5)P 3 (Domain and Waterfield, 1997). The PI3-K-dependent synthesis of PtdIns (3,4)P 2 and PtdIns (3,4,5)P 3 results in their accumulation in the inner leaflet of the plasma membrane and the subsequent membrane localization and activation of proteins that specifically bind these phosphatidylinositols; this colocalization and activation of enzymes along with their substrates allows for enhanced signaling activity within the cell resulting in marked modulation of cell phenotype and proliferation (Pacold et al, 2000). We have shown that 3-Cl-AHPC inhibits both AKT and ILK activities in addition to PI3-K in agreement with the proposed cascade of PI3-K activation of ILK and AKT.…”
Section: -Cl-ahpc Inhibits Akt-mediated Phosphorylation Of Fkhrmentioning
confidence: 99%
“…We have shown that 3-Cl-AHPC inhibits both AKT and ILK activities in addition to PI3-K in agreement with the proposed cascade of PI3-K activation of ILK and AKT. Class IA PI3-K is a heterodimer consisting of a 110 kDa (p110) catalytic subunit and a 85 kDa (p85) regulatory subunit (Pacold et al, 2000). Activation of PI3-K can occur through the binding of Ras, Rac, Rho, Cdc42 or specific phosphotyrosine proteins to specific domains (Carpentier et al, 1990;Yamamoto et al, 1992;Joly et al, 1994;Kapeller et al, 1994;Levy-Toledano et al, 1994).…”
Section: -Cl-ahpc Inhibits Akt-mediated Phosphorylation Of Fkhrmentioning
confidence: 99%